Mechanical Behaviour of Aluminium Hybrid Metal Matrix Composites – A Review. (2019) - Ravindran, S.; Mani, N.; Balaji, S.; Abhijith, M.; Surendaran, K.
Abstract: Metal composite materials have widespread application in different areas of daily life. Often it is not realized that the application makes use of composite materials. These materials are produced in situ from the conventional production and processing of metals. These high performance materials are used in both the airframe and propulsion systems that enable the modern aircraft to rotate larger degree while preserving its strength. In order to obtain sustained performance, designers are looking for lighter and stronger materials. The striking feature of aluminium is that it is relatively low at cost, light weight metal that can be heat treated to high strength levels and is one of the most easily fabricated high performance materials that comewith lower costs. In this review, the variation of the mechanical properties such as tensile strength, hardness, creep and fatigue for hybrid Aluminium metal matrix composites are compared and possible future studies need to be studied are concluded.